Improving Fungal Product Yield through Fast, Eco-friendly, and Cost-effective Chrom Genic Media Technology - Shaban, Abbas Dareb; Kadhim, Kadhim Fadhil; Shaaban, Ali Dhareb; Lafta, Saeed Jolan (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
The cost of commonly available culture media is a source of concern for many researchers, highlighting the need to explore more cost-effective alternatives or reduce the use of additives. Despite limited research in this area, efforts have been made to identify alternative culture media that are economically viable for cultivating microorganisms. This study explored the potential of beetroot extract as a cost-effective medium with col-or-inducing properties for fungal growth and as a chromogenic medium for testing lipase enzyme production efficiently as one of the rapid differential tests. The results indicated that Beetroot Agar Medium (BAM) offered significant cost savings in fungal cultivation while facilitating rapid fungal growth compared to other expensive and time-consuming media. Within a 3-4 day incubation period at a temperature range of 25-27 ˚C, all isolated fungi exhibited robust growth. Furthermore, the medium successfully served as a chromogenic differentiating medium by inducing fungi to produce lipase. These findings have broad implications for bio-technology and industrial applications, providing a sustainable and efficient alternative for microbial cultivation.